1996
DOI: 10.1021/ma960310v
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular Association and Supramolecular Organization in Dilute Solution. 2. Light Scattering and Optical Activity of Poly(p-biphenylylmethyl l-glutamate)

Abstract: Static and dynamic light scattering measurements are reported on dilute solutions of poly(p-biphenylylmethyl l-glutamate), PBPMG, in the helicogenic solvent THF, over a temperature range encompassing an observed reversible transition in the chiral optical properties of these solutions. The results confirm the expected helical conformation for this polypeptide, as well as complete dissolution of the polymer at temperatures above the transition temperature. Association is observed at lower temperatures, with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 46 publications
1
24
0
1
Order By: Relevance
“…These thermochromic changes have been observed previously for polythiophene solutions and films and have been ascribed to an improved packing of predominantly planar polymer chains. [7,11,21] In contrast to the changes observed in the absorption spectra of blend films, spin-coating a pure P3HT layer from chloroform directly leads to the optical features associated with the improved packing of the polymer chains. Annealing of such a pure P3HT layer did not significantly change the absorption features (data not shown).…”
Section: Photoconductivity Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…These thermochromic changes have been observed previously for polythiophene solutions and films and have been ascribed to an improved packing of predominantly planar polymer chains. [7,11,21] In contrast to the changes observed in the absorption spectra of blend films, spin-coating a pure P3HT layer from chloroform directly leads to the optical features associated with the improved packing of the polymer chains. Annealing of such a pure P3HT layer did not significantly change the absorption features (data not shown).…”
Section: Photoconductivity Measurementsmentioning
confidence: 99%
“…the polymer chain, is of crucial importance for the conduction of holes. These parameters are largely dependent on the deposition method of the PT layer [6,11] as well as on the PT regioregularity [7] and the annealing process. [3,4,12] Therefore, the hole mobility on PT chains within spin-coated films of PT/fullerene blends is difficult to predict, while the effect of additional treatments on the charge carrier dynamics, such as annealing or a chloroform-vapor treatment, [13] is even more unclear.…”
Section: Introductionmentioning
confidence: 99%
“…These parameters are largely dependent on the deposition method of the PT layer [5,11] as well as on the PT regioregularity [6] and the annealing process [2,3,12]. Therefore, the hole mobility on PT chains within spin-coated films of PT/ fullerene blends is difficult to predict, while the effect of additional treatments on the charge carrier dynamics, such as annealing or a chloroform vapor treatment [13] is even more unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In general, two forms may be encountered in the extreme: association involving two or more components at equilibrium at any give concentration; and metastable association, function of temperature is given in reference. (138) In the cited case, the scattering at any given temperature exhibited 'normal' behavior, and could not have been analyzed to reveal association if taken alone. In a different and somewhat unusual, but not unique, example, it has been reported that Kc/R Vv (ϑ,c) is linear in q 2 , albeit giving a molecular weight that is much larger than the true value of M w for the solute.…”
Section: Intermolecular Associationmentioning
confidence: 99%